The role of developing countries in global economic governance - Peter Lloyd (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2012)
The paper reviews critically the arguments concerning greater voice for developing countries in global governance. It supports the arguments for greater voice but argues that greater voice brings with it greater responsibilities in terms of the actions and commitments from developing countries. The two main illustrations are the multilateral trade negotiations in the WTO and the negotiations concerning climate change in the UN. In both case, it is argued, developing countries must assume greater responsibilities if these negotiations are to be concluded. This can be done in a way which yields net benefits to the developing countries themselves.
Keywords: F13; 330; global economic governance; developing countries; WTO; UNFCCC; Internationale Handelspolitik; Internationale Klimapolitik; Entwicklungsländer